2021
DOI: 10.1021/acs.jafc.0c07357
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Functional Analyses Indicate Novel Anti-viral Mode of Actions on Tobacco Mosaic Virus of a Microbial Natural Product ε-Poly-l-lysine

Abstract: Novel anti-viral natural product ε-poly-l-lysine (ε-PL) produced by Streptomyces is a homopolymer of l-lysine, of which the underlying molecular mode of action remains to be further elucidated. In this study, ε-PL induced significant fragmentation of tobacco mosaic virus (TMV) virions and delayed the systemic infection of TMV-GFP as well as wild-type TMV in plants. ε-PL treatment also markedly inhibited RNA accumulation of TMV in tobacco BY-2 protoplasts. The results of RNA-seq indicated that the agent induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The ε-PL was mainly applied to inhibit bacteria and was well-characterized as a food preservative [54]. In the previous study, we investigated the functions of ε-PL on the induction of host defense responses against the infection of the tobacco mosaic virus (TMV) [25], as well as the anti-fungal mechanisms of ε-PL on A. alternata [21]. The ε-PL was reported to effectively inhibit the incidence of grey mold rot on various fruits and vegetables caused by B. cinerea [23,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ε-PL was mainly applied to inhibit bacteria and was well-characterized as a food preservative [54]. In the previous study, we investigated the functions of ε-PL on the induction of host defense responses against the infection of the tobacco mosaic virus (TMV) [25], as well as the anti-fungal mechanisms of ε-PL on A. alternata [21]. The ε-PL was reported to effectively inhibit the incidence of grey mold rot on various fruits and vegetables caused by B. cinerea [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-bacterial activity of ε-PL was well investigated using Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa [17,19,20], while recent research focused on its effect on other plant pathogens, including viruses and fungi [21][22][23]. Our previous study showed that ε-PL significantly suppressed the infection of the tobacco mosaic virus (TMV) in Nicotiana glutinosa, as well as RNA accumulation in tobacco protoplasts and induced host defensive responses [24,25]. In addition, we indicated that ε-PL effectively inhibited vegetative growth and pathogenicity and affected the respective gene expression of Alternaria alternata [21].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with ε-PL in tobacco BY-2 protoplasts significantly downregulated Tobacco Mosaic Virus (TMV) RNA accumulation and induced the host defense response, suggesting ε-PL as a natural microbial to treat plant virus diseases [ 13 ]. In addition, ε-PL markedly inhibited Alternaria alternata disease progression by reducing germ tube elongation and spore germination and downregulating the expression of crucial fungal development-related genes [ 14 ]. In addition, the incidence of gray mold rot (caused by Botryris cinerea ) on a variety of fruit and vegetables was effectively inhibited by ε-PL [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reference gene EF-1a was used for quantitative analysis. The relative expression levels of the tested genes were calculated with the 2 −ΔΔCt method[27]. The primer sequences used are shown in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%